Information technology and library evolution - Tiwari, Purushotham (A. P. H. Publishing Corporation, 2006)
Contents of material: New technologies in library. Origins and motivation. Scope. Demand. Library resources.Preservation. Achival paradigm. Asset management. Right management. Audio/Video management. Quality assurance. Encoding of text. XML pointer language. Technology infrastructure. Service procurement in libraries. Online learners.